Body Image During Pregnancy in the Era of Coronavirus Disease 2019: The Role of Heterogeneous Patterns of Perceived Social Support - Piȩta, Małgorzata; Rzeszutek, Marcin; Lendzion, Michał; Grymowicz, Monika; Piȩta, Wojciech; Kasperowicz, Agata; Kucharski, Marek; Przybył, Mateusz; Smolarczyk, Roman (Frontiers in Psychology, 2021)
Objectives. The aim of this study was to explore profiles of pregnant women extracted on perceived social support with regards to sociodemographic variables, COVID-19 relating distress issues and body image. In addition, we compare aforementioned relationships within the study variables between pregnant women and control group with females without pregnancy. Method. The study sample comprised of 345 women, i.e., 157 pregnant women and 188 women from the control group. Participants filled out paper-and-pencil or on-line psychometric questionnaires to assess the variables analyzed in our research. Results. Latent profile analysis revealed six profiles of pregnant based on perceived social support that varied in terms of body image evaluation. The high-support profile differed significantly from the profile with the lowest scores in all support domains. Also, significant differences in body image between extracted profiles and control group was noted. Conclusions. Understanding the mechanisms through which women can gain more body satisfaction during pregnancy is an important research perspective which can inspire planning for more effective psychological help, especially in the context of the consequences of COVID-19 pandemic and related psychological distress.